Analisis Penyerapan Tenaga Kerja Sektor Industri Manufaktur 9 Provinsi di Indonesia Periode 2011-2021 - Novika Nurkhasanah; Gea Dwi Asmara; Indanazulfa Qurrota A’yun (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
Over time, Indonesia's population has steadily increased, primarily driven by a growing workforce. However, without effective employment opportunities, this growth can lead to high unemployment rates. One sector that plays a pivotal role in absorbing this workforce is the manufacturing industry, which happens to be Indonesia's largest contributor to GDP. This empirical study delves into the factors influencing labor absorption in the manufacturing sector, including Gross Regional Domestic Product (GRDP), Regional Minimum Wage (UMP), Human Development Index (HDI), average years of schooling, and the number of companies. Data for this research is sourced from the official website of the Central Statistics Agency (BPS) and analyzed using Seemingly Unrelated Regression (SUR) on cross-sectional data spanning from 2011 to 2021. The study encompasses nine Indonesian provinces: North Sumatra, Riau, South Sumatra, DKI Jakarta, West Java, Central Java, East Java, Banten, and Riau Islands. Results indicate that GRDP, HDI, and the number of companies positively and significantly impact labor absorption, while UMP and average years of schooling exhibit negative and significant effects on labor absorption.